2012
DOI: 10.4269/ajtmh.2012.12-0030
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Motivation and Retention of Community Health Workers Delivering Integrated Community Case Management (iCCM): Stakeholder Perceptions and Priorities

Abstract: Despite resurgence in the use of community health workers (CHWs) in the delivery of community case management of childhood illnesses, a paucity of evidence for effective strategies to address key constraints of worker motivation and retention endures. This work reports the results of semi-structured interviews with 15 international stakeholders, selected because of their experiences in CHW program implementation, to elicit their views on strategies that could increase CHW motivation and retention. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(162 citation statements)
references
References 18 publications
8
147
1
6
Order By: Relevance
“…A study in Uganda noted that if the community health workers did not receive prompt responses from the end-user, or if they had an issue that was never resolved, they would become demoralized [37]. mHealth can also affect the ways front-line users feel about their jobs, with one group of community health workers reporting that the use of mobile technology for data collection distanced them from the human aspect of their job, and turned them into ‘data collection robots’ [38]. …”
Section: User Considerationsmentioning
confidence: 99%
“…A study in Uganda noted that if the community health workers did not receive prompt responses from the end-user, or if they had an issue that was never resolved, they would become demoralized [37]. mHealth can also affect the ways front-line users feel about their jobs, with one group of community health workers reporting that the use of mobile technology for data collection distanced them from the human aspect of their job, and turned them into ‘data collection robots’ [38]. …”
Section: User Considerationsmentioning
confidence: 99%
“…Traditionally, there are differences in the activities performed by, and duties expected of, paid and volunteer CHWs [16]. It has been suggested that policymakers may be concerned that financial incentives which are perceived as too low, are paid irregularly, or are terminated due to fluctuations in funding may be more of a disincentive to CHWs than no payment at all [17,18]. There is, however, evidence from Haiti and Brazil that irregularities in payment need not be detrimental providing sufficient institutional effort is put into managing available funding and staff motivation [14,19].…”
Section: Introductionmentioning
confidence: 99%
“…La salud móvil (mHealth) es un área de salud electrónica (eHealth) que provee: a) servicios sanitarios e información utilizando las tecnologías móviles, y b) servicios de diseminación de la información respecto a actualizaciones sanitarias, materiales didácticos, y recordatorios. El mHealth está abriendo un mundo de oportunidades en el ámbito de la salud pública, en particular en los países con recursos limitados como Paraguay (Mechael, 2009;UNDP, 2012b;Strachan, Källander, Ten Asbroek, Kirkwood, Meek, Benton & Hill, 2012).…”
Section: Introductionunclassified